Os fundamentos da objetividade das representações em Kant - Tomasel, Juliano (2012)
This work is intended to discuss Kant's reflections and responses to the problem of the objectivity of representations. This issue that is the central theme of the Transcendental Analytic of the Critique of Pure Reason, is strongly focused on the distinction between sensible and intellectual conditions, intuitions and concepts, which constitute the fundamental elements of our experience. The experience is determined by the way our representations are referred to objects. The objects of experience are the objective contents of our representations, constituted by intuitions and concepts. The first ones are immediate and singular representations of objects the latter are mediate rules that determine the data of intuitions by general characteristics. Therefore, it s necessary that intuitions are described by concepts, which are universal representations. By means of writings of Metaphysical Deduction and Transcendental Deduction, I intended to rebuild the arguments provided for Kant to support the idea that reference to intuitions is necessary and universally held by the rules that derive a priori of the understanding and not by mere accident. These rules are the pure concepts of understanding or categories. The Metaphysical Deduction is the argument used by Kant to present the complete list of these categories by derivation of the universal logical functions of thought. These functions are the elementary forms of judgments because the judgments represent the forms of thought or the relations in which different representations are brought to unity of thought. In the Transcendental Deduction, at first, Kant seeks to demonstrate that the pure concepts of understanding are a priori rules of the reference of thought to objects of a sensible intuition in general. Secondly, the argument is directly addressed to the specific conditions of our sensible intuition, with the intention of asserting that all sensible representations must be determined in own intuition by means categories.